On Ethics and the Earthquake Resistant Interior Design of Buildings. - Hurol, Yonca (Science & Engineering Ethics, 2014)
The most common tectonic quality of modern structures, such as frame systems, is their flexibility; they are open for change. Although this characteristic is a big advantage in comparison to the inflexible masonry structures of the past, it might also create some serious problems, such as e.g. the lack of safety in the event of an earthquake, if the flexibility is not used consciously by architects and interior designers. This article attempts to define and establish some rules for the interior design of buildings with reinforced concrete frame systems. The rules for making subtractions from these structures and extending them by making additions to them are contained within this article. The main objective of this article is to derive some ethical values from these rules. Thus, the conclusion of the article focuses on the derivation of some ethical values for achieving earthquake resistant interior design of buildings with reinforced concrete frame systems.